The Conception of Values by Lithuanian Neo-Thomists - Buišytė, Dalia Marija (Problemos, 1979)
Neo-Thomists consider value to be defined by the man’s divine soul. Science is said to be inconsistent to present a complete description of being. It is the Marxist methodology that applies a scientific method to explain society its history and man. The subject of cognition thus becomes real.